MOTIVATIONAL DYNAMICS OF WEARABLE ACTIVITY MONITORS. (September 2017) - Lyons, Elizabeth J.; Swartz, Maria C.
Abstract : Apply It!: By reading this article the health and fitness professional will Learn about methods for comparing different wearable activity tracking monitor systems Be able to use behavior change techniques and gamification elements to understand the apps that are used with these monitors